2016
DOI: 10.15302/j-fase-2016125
|View full text |Cite
|
Sign up to set email alerts
|

The secondary laticifer differentiation in rubber tree is induced by trichostatin A, an inhibitor of histone acetylation

Abstract: The secondary laticifer, a specific tissue in the secondary phloem of rubber tree, is differentiated from the vascular cambia. The number of the secondary laticifer in the trunk bark of rubber tree is positively correlated with rubber yield. Although jasmonates have been demonstrated to be crucial in the regulation of secondary laticifer differentiation, the mechanism for the jasmonate-induced secondary laticifer differentiation remains to be elucidated. By using an experimental morphological technique, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Besides this, we found three genes (TAZ, GNAT, and SNF2) in the FDE dataset that are related to histone acetylation. The specific patterns of histone acetylation could alter the rate of chromatin remodelling in many ways 112 and in particular, a histone deacetylase inhibitor, Trichostatin A, was reported to induce induce SLD in H. brasiliensis 24 . This further suggests the importance of histone acetylation in the regulation of SLD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides this, we found three genes (TAZ, GNAT, and SNF2) in the FDE dataset that are related to histone acetylation. The specific patterns of histone acetylation could alter the rate of chromatin remodelling in many ways 112 and in particular, a histone deacetylase inhibitor, Trichostatin A, was reported to induce induce SLD in H. brasiliensis 24 . This further suggests the importance of histone acetylation in the regulation of SLD.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, wounding which is often done during commercial exploitation, is an important factor that induces laticifer ring formation 20,21 . In addition, the application of exogenous jasmonic acid (JA), methyl jasmonate, linolenic acid (LA), hydrogen peroxide, polyethylene glycol 6000, trichostatin A, or coronatine could induce the secondary laticifer differentiation (SLD) in H. brasiliensis but this is not the case for ethylene, salicylic acid or abscisic acid treatment 18,2224 . Among the factors that could induce SLD, JA is a phytohormone where its signalling pathway has been studied extensively 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are many reports about the effect of methyl jasmonate on development of laticifers, for example, inducing the biosynthesis of secondary plant metabolites and stimulating the formation and differentiation of milk ducts [11,12]. On this basis, comparative proteomics studies of latex in E. kansui laticifers treated with methyl jasmonate were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…MeJA promotes the transcription and expression of the vegetative storage protein (VSP) in Medicago sativa [11], and also induces the biosynthesis of secondary plant metabolites. It has been reported that exogenous JAs can stimulate formation and differentiation of laticifers, a specific type of cell, in Hevea brasiliensis , and they can induce the production of numerous secondary metabolities, including latex [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The number of the secondary laticifers in the trunk bark is closely related to the rubber yield. The secondary laticifer is differentiated from vascular cambia (Hao and Wu, 2000 [6]), and induced by such factors as jasmonic acid (JA) [6][7][8], mechanical wounding [7], and coronatine (COR) [9][10][11], an active jasmonate homolog [12] Available data show that both the secondary laticifer differentiation [6,13] and the rubber biosynthesis [14] are positively controlled by JA signalling. Therefore, the MYC members in rubber trees should be involved in regulating Forests 2022, 13, 531 2 of 13 such processes.…”
Section: Introductionmentioning
confidence: 99%